Women Empowerment in Veterinary Field: A Review - Dr. Madhuri Lahamge , Dr. Ankita Thakar, Dr. Sonali D.Borkar , Dr.Shiny Joy , (International Journal of Scientific Research and Management (IJSRM), 2017)
Women Empowerment itself elaborates that Social Rights, Political Rights, Economic stability, judicialstrength and all other rights should be also equal to women. There should be no discrimination betweenmen and woman. In fact animal Husbandry is becoming feminized. About 70% of the agriculturalworkers, 69% of workforce engaged in livestock sector and 80% of the food a strong desire to dosomething positive is an inbuilt quality of entrepreneurial women, who is capable of contributing valuesin both family and social life. Women should now there fundamental and social rights which they getonce they born. Empowering women to participate fully in economic life across all sectors is essential tobuild stronger economies, achieve internationally agreed goals for development and sustainability, andimprove the quality of life for women, men, families and communities.